Nanotheranostics: Molecular Diagnostics and Nanotherapeutic Evaluation by Photoacoustic/Ultrasound Imaging in Small Animals - Dhamija P.; Mehata A.K.; Setia A.; Priya V.; Malik A.K.; Bonlawar J.; Verma N.; Badgujar P.; Randhave N.; Muthu M.S. (My University, 2025)
Nanotheranostics is a rapidly developing field that integrates nanotechnology, diagnostics, and therapy to provide novel methods for imaging and treating wide categories of diseases. Targeted nanotheranostics offers a platform for the precise delivery of theranostic agents, and their therapeutic outcomes are monitored in real-time. Presently, in vivo magnetic resonance imaging, fluorescence imaging, ultrasound imaging, and photoacoustic imaging (PAI), etc. are noninvasive imaging techniques that are preclinically available for the imaging and tracking of therapeutic outcomes in small animals. Additionally, preclinical imaging is essential for drug development, phenotyping, and understanding disease stage progression and its associated mechanisms. Small animal ultrasound imaging is a rapidly developing imaging technique for theranostics applications due to its merits of being nonionizing, real-time, portable, and able to penetrate deep tissues. Recently, different types of ultrasound contrast agents have been explored, such as microbubbles, echogenic exosomes, gas-vesicles, and nanoparticles-based contrast agents. Moreover, an optical image obtained through photoacoustic imaging is a noninvasive imaging technique that creates ultrasonic waves when pulsed laser light is used to expose an object and creates a picture of the tissue’s distribution of light energy absorption on the object. Contrast agents for photoacoustic imaging may be endogenous (hemoglobin, melanin, and DNA/RNA) or exogenous (dyes and nanomaterials-based contrast agents). The integration of nanotheranostics with photoacoustic and ultrasound imaging allows simultaneous imaging and treatment of diseases in small animals, which provides essential information about the drug response and the disease progression. In this review, we have covered various endogenous and exogenous contrast agents for ultrasound and photoacoustic imaging. Additionally, we have discussed various drug delivery systems integrated with contrast agents for theranostic application. Further, we have briefly discussed the current challenges associated with ultrasound and photoacoustic imaging. © 2023 American Chemical Society.